The ubiquitin-like modifier FAT10 interferes with SUMO activation - Aichem, Annette; Stankovic-Valentin, Nicolas; Melchior, Frauke (Nature Communications, 2019)
The covalent attachment of the cytokine-inducible ubiquitin-like modifier HLA-F adjacent transcript 10 (FAT10) to hundreds of substrate proteins leads to their rapid degradation by the 26 S proteasome independently of ubiquitylation. Here, we identify another function of FAT10, showing that it interferes with the activation of SUMO1/2/3 in vitro and down-regulates SUMO conjugation and the SUMO-dependent formation of promyelocytic leukemia protein (PML) bodies in cells. Mechanistically, we show that FAT10 directly binds to and impedes the activity of the heterodimeric SUMO E1 activating enzyme AOS1/UBA2 by competing very efficiently with SUMO for activation and thioester formation. Nevertheless, activation of FAT10 by AOS1/UBA2 does not lead to covalent conjugation of FAT10 with substrate proteins which relies on its cognate E1 enzyme UBA6. Hence, we report that one ubiquitin-like modifier (FAT10) inhibits the conjugation and function of another ubiquitin-like modifier (SUMO) by impairing its activation.